Determination of difference between freshman and senior-level of psychology students in terms of the eating attitudes and psychological symptoms - Karayagiz, Saban (Progress in Nutrition, 2020)
Aim: Eating disorder (ED) is a deviation in eating habits that are based on insufficient or overeating and mental influences, causing serious problems such as anxiety. In recent years, some physical appearances have become more prominent in social settings such as TV and social media. The purpose of this study was to investigate the impacts of appearance with body dissatisfaction, perfectionism levels, and psychological symptoms of the university students on the eating attitude enrolled at the department of psychology. Particularly, it focused on whether any changes in the attitudes towards eating habits could change after psychology education in college. Method: Data was collected from the psychology students at their freshman in 2015 and senior years in 2019 by utilizing a longitudinal study methodology. Data collection tools contained Positive and Negative Perfectionism Scale (PNPS), Social Appearance Anxiety Scale (SAAS), Brief Symptom Inventory (BSI), and the Eating Attitudes Test (EAT). Study Group: A total of 53 college students were included in the study. Most of them (N=40, 75.6%) were female and few (N=13, 24.5%) were male. The average ages of the students were found 20.6(2015 sd parameter 1.8, 2019 sd parameter 1.7) years old during the data collection process. Results and Discussion: The findings showed that male students achieved lower scores than females in terms of eating habits (EAT) and psychological symptoms (BSI), and higher on appearance anxiety levels (SAAS) based on the results of the pretest and posttest sessions.